Uji Hedonik Produk Hard Biscuit Pada Tepung Pisang Dengan Metode Annealing Dan Retrogradasi - Ruhil Fida (Jurnal Prodi Agribisnis, 2022)
This study aims to determine the hedonic test conducted by panelists of hard biscuit products using annealing and retrogrdation modified banana flour. Consisting of three treatments, each treatment was repeated 6 times. The results showed that the hard biscuit color hedonic test of Hard biscuit treatment A, namely 100% wheat flour, had an average score of 4.94. Hard biscuit treatment B has an average score of 3.74 and hard biscuit treatment C has an average score of 3.02. In the texture hedonic test, hard biscuit treatment A had a mean score of 4.43, while hard biscuit treatment B had a mean score of 3.77 (somewhat dislike) and hard biscuit treatment C had a mean score of 3.52 (somewhat dislike). The hedonic test of hard biscuit aroma of treatment A has a mean score of 4.50 (like), while hard biscuit treatment B has a mean score of 3.83 (somewhat like) and hard biscuit treatment C has a mean score of 3.45 (somewhat dislike). Meanwhile, the hedonic test of hard biscuit flavor treatment A has a mean score of 4.72 (like), while hard biscuit treatment B has a mean score of 3.74 (somewhat like) and hard biscuit treatment C has a mean score of 3.41 (somewhat dislike).